Eat, pray, love one woman's search for everything across Italy, India, and Indonesia - Gilbert, Elizabeth, 1969- (Detroit : Thomson Gale, 2007)
"'Elizabeth Gilbert, a successful writer, had everything -- a husband, friends, a big house in New York. But one day she realized she did not want any of it. Her marriage broke down, and she went through a long, painful divorce. A new relationship brought more heartbreak, deep depression followed, and in desperation, she started to pray. She decided to spend a year without any new relationships, and to travel to Italy, India, and Indonesia, searching for meaning in her life. This memoir is the true story of her journey of discovery through pleasure, religion, and back to love again."
"Large Print Press."
Keywords: Gilbert, Elizabeth, -- 1969- -- Travel; Travel writers -- United States -- Biography; Self-realization in women; Large type books